Impact of the COVID-19 Pandemic on Births, Vaginal Deliveries, Cesarian Sections, and Maternal Mortality in a Brazilian Metropolitan Area: A Time-Series Cohort Study - Ferreira DP; Bolognani CV; Santana LA; Soares Fernandes SES; de Moraes MSF; Fernandes LAS; Pereira CDS; Ferreira GB; Göttems LBD; Amorim FF (Dove Medical Press, 2023)
Dilson Palhares Ferreira,1,* Cláudia Vicari Bolognani,2,3,* Levy Aniceto Santana,2,* Sérgio Eduardo Soares Fernandes,2,3,* Matheus Serwy Fiuza de Moraes,3,* Luana Argollo Souza Fernandes,3,* Camila de Sousa Pereira,3,* Gabriela Billafan Ferreira,3,* Leila Bernarda Donato Göttems,2,3,* Fábio Ferreira Amorim1- 4,* 1Graduation Program in Health Sciences, University of Brasília (UnB), Brasília, Federal District, Brazil; 2Department of Research and Scientific Communication, Escola Superior de Ciências da Saúde (ESCS), Brasília, Federal District, Brazil; 3Medical School, Escola Superior de Ciências da Saúde (ESCS), Brasília, Federal District, Brazil; 4Graduation Program in Health Sciences of School Health Sciences, Escola Superior de Ciências da Saúde (ESCS), Brasília, Federal District, Brazil*These authors contributed equally to this workCorrespondence: Fábio Ferreira Amorim; Dilson Palhares Ferreira, Coordenação de Pesquisa e Comunicação Científica - Escola Superior de Ciências da Saúde, SMHN Quadra 03, conjunto A, Bloco 1 - Edifício FEPECS, Brasília, Federal District, CEP 70701-907, Brazil, Email ffamorim@gmail.com; palhares.dilson@gmail.comPurpose: The COVID-19 pandemic posed a worldwide challenge, leading to radical changes in healthcare. The primary objective of the study was to assess the impact of the COVID-19 pandemic on birth, vaginal delivery, and cesarian section (c-section) rates. The secondary objective was to compare the maternal mortality before and after the pandemic.Patients and Methods: Time-series cohort study including data of all women admitted for childbirth (vaginal delivery or c-section) at the maternities in the Public Health System of Federal District, Brazil, between March 2018 and February 2022, using data extracted from the Hospital Information System of Brazilian Ministry of Health (SIH/DATASUS) on September 30, 2022. Causal impact analysis was used to evaluate the impact of COVID-19 on birth, vaginal delivery, and c-section using the CausalImpact R package, and a propensity score matching was used to evaluate the effect on maternal mortality rate using the Easy R (EZR) software.Results: There were 150,617 births, and considering total births, the effect of the COVID-19 pandemic was not statistically significant (absolute effect per week: 5.5, 95% CI: − 24.0− 33.4). However, there was an increase in c-sections after COVID-19 (absolute effect per week: 18.1; 95% CI: 11.9− 23.9). After propensity score matching, the COVID-19 period was associated with increased maternal mortality (OR: 3.22, 95% CI: 1.53− 6.81). The e-value of the adjusted OR for the association between the post-COVID-19 period and maternal mortality was 5.89, with a 95% CI: 2.43, suggesting that unmeasured confounders were unlikely to explain the entirety of the effect.Conclusion: Our study revealed a rise in c-sections and maternal mortality during the COVID-19 pandemic, possibly due to disruptions in maternal care. These findings highlight that implementing effective strategies to protect maternal health in times of crisis and improve outcomes for mothers and newborns is crucial.Keywords: COVID-19, cesarean section, maternal health services, maternal mortality